Intelligent Integrated Digital Platform InSilicoKDD in Support of Precision Medicine for Scientific Research - lamenka Borovska, Iliyan Kordev, Boris Borowsky (International Journal of Advanced Science and Technology, 2020)
The paper presents intelligent integrated digital platform InSilicoKDD based on scientific workflowsin support of precision medicine designed, implemented and deployed at the Faculty of AppliedMathematics and Informatics, Technical University of Sofia. The platform is built upon our method foradaptive in silico knowledge data discovery and intelligent decision making as well as integratedapproach to combine and analyze digital data at all stages of breast cancer progress, deployingmodern in silico KDD methods and technologies. The conceptual architectural design of InSilicoKDDplatform is presented and the software prototype revealed. Functionality and efficiency ofInSilicoKDD platform have been verified on the basis of experimentation for the breast cancer issue byconfiguring and executing scientific workflows encompassing machine learning models for diagnosticsand prediction, data sets with results of the biopsy of the cells in the patient's tumor as well as breastcancer risk assessment models